2022
DOI: 10.3892/mmr.2022.12876
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‑dependent activation of PHEX, MEPE and DMP1 in osteocytes

Abstract: Calcium (Ca 2+ ) signaling is the first messenger signal exhibited by osteocytes. The present study aimed to better understand the link between Ca 2+ concentration, and the levels of bone mineralization regulator proteins [phosphate-regulating neutral endopeptidase on chromosome X (PHEX), matrix extracellular phosphoglycoprotein (MEPE) and dentin matrix protein 1 (DMP1)] and the levels of oxidative stress in osteocytes. The viability of MLO-Y4 cells was determined using the live/dead assay following treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Understanding the metabolism of these proteins is crucial because PHEX and MEPE depletion or inactivation can lead to some serious clinical issues. Donmez BO et al suggest that different calcium concentrations can trigger bone mineralization proteins such as PHEX, MEPE, and DMP1 in osteocytes [48]. Our results showed that there is an antagonistic behavioral modulation between the MEPE and PHEX correlated with previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…Understanding the metabolism of these proteins is crucial because PHEX and MEPE depletion or inactivation can lead to some serious clinical issues. Donmez BO et al suggest that different calcium concentrations can trigger bone mineralization proteins such as PHEX, MEPE, and DMP1 in osteocytes [48]. Our results showed that there is an antagonistic behavioral modulation between the MEPE and PHEX correlated with previous studies.…”
Section: Discussionsupporting
confidence: 87%